Extreme climate variability weakens a major tropical agricultural hub. (April 2020) - González-Orozco, Carlos E.; Porcel, Mario; Alzate Velásquez, Diego F.; Orduz-Rodríguez, Javier O.
Highlights: The agro-climatic zonification of citrus is the first one of its kind in Colombia. Citrus are good indicators of ecological risk in the eastern plains of Colombia. Extreme climate variability affected the climatic space of the citrus growing regions. High citrus production areas in the Orinoquia region are under high vulnerability. The most important agricultural hub of Bogota faces new management challenges. Abstract: Agriculture is affected daily by climatic phenomena, but limited information is available on the impacts of extreme climate variability (ECV) in agricultural systems of tropical countries. Citrus was used as a model system to explore whether ECV scenarios cause severe impacts on the climatic suitability of the crop in the eastern plains of Colombia, a key agricultural hub for the country. Because this region is a national food basket, climate risks need to be identified across the territory. Our study developed species distribution modelling of citrus used to generate the first agro-climatic zonification for citrus in Colombia. We used this model to investigate the interannual ECV impacts based on the latest ensemble modelling approaches. The ECV scenarios in this study are unique and highly valuable because we analyze maximum and minimum interannual values recorded daily from 1980 to 2010 rather than monthly. Four citrus growing climatic zones were identified. In the worst-case scenarios, these zones experienced a loss of climatically suitable area by 50%. However, in some cases optimum areas remained unchanged and/or new suitable areas emerged. Strong rainfall and high temperatures triggered negative impacts in the most critically-affected zones, weakening a large proportion of the ideal climatic space for citrus growing. Our study provides new evidence that could be used to generate climate-based ecological indicators for regions of high vulnerability. Delimitation maps and modelling results may be used by citrus growers to develop more efficient citrus production systems in tropical conditions and ultimately increase resilience to climate variability.